Determinants of Financial Reporting Quality: Internal Control Effectiveness, IT Utilization and Tax Compliance with Human Resource Capability as Moderator - Yohanes Mardinata Rusli; Andrianto Widjaja (Greenation Research & Yayasan Global Resarch National, 2026)
Financial Reporting Quality (FRQ) remains a critical issue in healthcare organizations due to complex financial transactions regulatory demands and increasing requirements for transparency and accountability. This study examines the effects of Internal Control Effectiveness (ICE) Information Technology Utilization (ITU) and Tax Compliance (TAC) on FRQ and the moderating role of Human Resource Capability (HRC). A quantitative cross-sectional survey design was used involving accounting finance and internal audit personnel from JCI-accredited private hospitals in Jakarta and Tangerang Indonesia. Of the 220 distributed questionnaires 203 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that ICE TAC and HRC significantly improve FRQ while ITU has no significant effect. Moreover HRC strengthens the relationships between ICE and FRQ as well as TAC and FRQ but does not moderate ITU’s effect on FRQ. These findings indicate that technology adoption alone is insufficient to enhance FRQ without strong governance mechanisms and capable human resources. The study contributes to literature by highlighting complementary roles of internal controls tax compliance and human resource capability in improving reporting quality in healthcare organizations. Practical implications are provided for strengthening organizational accountability, governance effectiveness, and long-term institutional sustainability.